THE STATE OF ANTIOXIDANT SYSTEM OF RATS’ ORGANISM UNDER CONTINUOUS CADMIUM AND LEAD LOAD - Слободян, С. О.; Gutyj, B. V. (Scientific Progress & Innovations, 2020)
Heavy metals lead and cadmium are dangerous environmental pollutants. The mechanism of these poisons’ action consists in inhibiting the activity of enzyme systems by blocking carboxyl, amine and SH groups of protein molecules. The aim of the study was to investigate the state of antioxidant protection system of rats under long cadmium and lead load. The system of rats’ organism antioxidant protection was investigated on the basis of in- dices of enzymatic and non-enzymatic elements, namely: catalase, superoxide dismutase activity and the level of reduced glutathione. The experiments were performed on male Wistar line rats weighing 200–220 g, of which 4 groups of animals were formed: control group - they were injected drinking water through a metal probe in a volume equivalent to the volume of aqueous solution of Cd2+ and Pb2+ salts; experimental group 1 – the animals were administered a 0.029 % aqueous solution of cadmium chloride at a dose of 4.0 mg/kg; experimental group 2 – the animals were administered 16.6 % aqueous lead acetate solution at a dose of 200 mg/kg; experimental group 3 – the animals were administered 16.6 % aqueous lead acetate solution at a dose of 100 mg/kg and 0.029 % aqueous cadmium chloride solution at a dose of 2.0 mg/kg. Introducing cadmium chloride to the rats’ organism contributed to a more likely decrease in antioxidant protection system indices in their blood than the administration of lead acetate. This decrease in antioxidant activity was stipulated by the ability of cadmium ions to inhibit the activity of these enzymes to a greater extent than lead ions, but the combined effect of the two studied metals was more pronounced. On the fourteenth day of the experiment, under combined introduction of heavy metals, the lowest activity of the antioxidant protection system was registered in the blood of rats in the third ex- perimental group. On the twenty-first day of the experiment, catalase and superoxide dismutase activity in the blood of rats with lead-cadmium load decreased by 19.7 and 25.2 %, whereas the level of reduced glutathione decreased by 24.4 %, respectively. The conducted investigations made it possible to reveal more deeply the path- ogenesis of cadmium and lead toxic effects on rats’ organism and use the obtained data in the development of antidote for cadmium-lead intoxication.